New interpretation technique for tracer well tests - K. M. Fedorov; A. P. Shevelev; A. Y. Gilmanov; A. A. Izotov; A. V. Kobyashev (Известия высших учебных заведений: Геология и разведка)
Background. Tracer well tests were proposed in the last century as an approach for elaboration of detailed reservoir models. Such tests implied injecting weakly adsorbable tracers into an injection well followed by collection and analysis of samples in nearby production wells. The results were assumed to clarify well connectivity and inter-well hydraulic conductivity. However, practical application of these tests showed that the tracer penetrates into the production well much faster than predicted from estimates of the reservoir properties.Aim. To develop a new technique for interpreting the results of tracer well tests.Materials and methods. The process of tracer movement along a self-induced hydraulic fracture was simulated taking into account the mass transfer parameter. The developed algorithm for interpreting the results of tracer studies was tested in a deposit located in Western Siberia. The productive interval is located in the Jurassic interval of the Vasyugan Formation. An aqueous solution of thiocarbamide with a concentration of 9% was used as a tracer. Injection was carried out through injection well XX74 for 3 h. The mass of the injected tracer was 1 t. Measurements in six reacting production wells XX72, XX73, XX75, XX76, XX77, and XX78 were conducted for 75 days. During this time period, 516 samples were collected. In the first three days, 36 samples were extracted at equal time intervals; in the following two weeks, 90 samples were extracted also at equal time intervals; during the remaining days, measurements were conducted 2—3 times per week for each well. The results of the conducted studies were interpreted based on the developed methodology for all the wells.Results. A numerical and analytical solution of the problem of tracer slug movement along the fracture was obtained. Account was taken of the mass transfer between the fluids and the layer, as well as the dissipation of the tracer slug. This solution was used as the basis for a new technique for interpreting the results of tracer well tests, which allows a greater number of fracture parameters to be determined.Conclusion. The developed technique for determining the parameters of technogenic fractures was applied in practice. The presence of several fractures connecting injection and production wells is shown. It is established that the process of formation of such fractures in the reservoir is still ongoing.